Pendekatan CPTED untuk Identifikasi Ruang Rawan di Perguruan Tinggi : Studi Kasus: Kampus II UAJY - Maria Vika Wirastri; Anak Agung Ayu Ratih Tribhuana Adityadewi Karang (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Violence in higher education environments has become an increasingly prominent issue, alongside the rising number of reported cases of physical, psychological, and sexual violence in educational settings. This community service project was conducted to map vulnerable and safe spaces at Campus II of Universitas Atma Jaya Yogyakarta (UAJY) as a preventive approach grounded in spatial design. The activities included physical mapping of the campus area, field observations, discussions with key stakeholders, and validation of users’ perceptions through questionnaires distributed to members of the academic community. The results indicate that vulnerable spaces are generally associated with areas characterised by limited surveillance, insufficient lighting, and a lack of positive social activities, such as poorly lit corridors, service areas and toilets, transitional spaces between buildings, and basement areas. In contrast, safe spaces are defined by visual openness, positive activities, and a strong sense of user ownership. This project produced maps of vulnerable and safe spaces, as well as design guidelines for safe spaces, based on the principles of Crime Prevention Through Environmental Design (CPTED), contextualised for the Indonesian campus environment. The novelty of this community service lies in integrating spatial mapping, user perception analysis, and practical design recommendations as policy inputs for violence prevention in higher education institutions.